Planning for change, long term: The 100-year plan. (December 2022) - Francis, Anna
This article draws on the place-based practice as research work of Associate Professor Anna Francis, to consider an alternative model for developing long-term approaches to creative community development. Francis's research into the effects of having professional arts practitioners facilitate public-participatory art within community development and urban regeneration initiatives has led to specific types of impact: fostering community development and cohesion in underprivileged areas of Stoke-on-Trent; influencing local government policy; and developing new initiatives and cultures in social arts organisations. A key part of that work has focused on the development of The Portland Inn Project since 2015, a creative artist and community led regeneration initiative, in a deprived area of Stoke-on-Trent, supporting community members to make positive change and development, via an embedded and varied arts development programme. Since 2021, The Portland Inn Project has developed thinking and action around the development of a Community Led 100-year plan for the neighbourhood. The 100-year plan borrows from landscape architecture and design thinking to empower communities, funders and policy makers to resist short-term project-based thinking, and to begin to think more holistically and sustainably, which can have significant benefits, socially, politically and environmentally.